Enhancing Vibrio vulnificus infection diagnosis for negative culture patients with metagenomic next-generation sequencing - Li, Xinghua; Wang, Chengzhuo; Guo, Zhaowang; Xiao, Tongyang; Ji, Yuxin; Ma, Yongguang; Li, Meiyi; Xia, Jinyu; Liu, Xi (Frontiers in Cellular and Infection Microbiology, 2023)
Objective To evaluate the diagnostic value of metagenomic next-generation sequencing (mNGS) in Vibrio vulnificus (V. vulnificus) infection. Methods A retrospective analysis of patients with V. vulnificus infection at the Fifth Affiliated Hospital of Sun Yat-Sen University from January 1, 2020 to April 23, 2023 was conducted. 14 enrolled patients were diagnosed by culture or mNGS. The corresponding medical records were reviewed, and the clinical data analyzed included demographics, epidemiology laboratory findings, physical examination, symptoms at presentation, antibiotic and surgical treatment, and outcome. Results In this study, 78.6% (11/14) patients had a history of marine trauma (including fish stab, shrimp stab, crab splints and fish hook wounds), 7.1% (1/14) had eaten seafood, and the remaining 14.3% (2/14) had no definite cause. Isolation of V. vulnificus from clinical samples including blood, tissue, fester and secreta. 9 cases were positive for culture, 5 cases were detected synchronously by mNGS and got positive for V. vulnificus. 85.7% (12/14) cases accepted surgical treatment, with 1 patient suffering finger amputated. 14 enrolled patients received appropriate antibiotic therapy, and all of them had recovered and discharged. 9 strains V. vulnificus isolated in this study were sensitive to most beta-lactam antibiotics, aminoglycosides, quinolones, etc. Conclusion Vibrio vulnificus infection is a common water-exposed disease in Zhuhai, which requires identification of a number of pathogens. Of severe infections with unknown pathogen, mNGS can be used simultaneously, and the potential to detect multiple pathogens is of great help in guiding treatment.